Detection method for corrosion resistance of SiC-C base and application of detection method
By depositing a dot-like transition metal film on the surface of the SiC-C base sample block and corrosion in the mixed airflow of HCl and H2, the corrosion depth is measured to judge the corrosion resistance, the problem of low efficiency of existing detection methods is solved, and fast and accurate corrosion resistance detection is achieved.
Patent Information
- Application Number
- CN202510183281.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-02-19
AI Technical Summary
The existing SiC-C base corrosion resistance detection methods are inefficient and have a long hydrothermal corrosion cycle, which cannot meet the actual application needs.
By depositing a dot-like transition metal film distributed with dot matrix on the surface of the SiC-C base sample block and corrosion in the mixed airflow of HCl and H2, the corrosion depth is measured to judge the corrosion resistance.
This method can quickly and accurately detect the corrosion resistance of SiC-C base, with the corrosion rate reaching 0.146×10-2~0.302×10-2μm/min, significantly improving the detection efficiency.
Smart Images

Figure HDA0005277756850000011 
Figure HDA0005277756850000012 
Figure HDA0005277756850000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of chemical detection, and in particular to a method for detecting the corrosion resistance of a SiC-C base and an application thereof. Background Art
[0002] Si-based chips are integrated circuit chips made of silicon materials. The silicon substrate is obtained by epitaxial growth of wafers. Currently, metal organic chemical vapor deposition is commonly used to achieve epitaxial growth of silicon substrates. SiC coated graphite base is one of the core components in metal organic chemical vapor deposition equipment. It is in direct contact with the substrate and plays a role in supporting and heating the silicon substrate. It has good chemical stability and high mechanical properties at high temperatures.
[0003] When epitaxial growth is carried out on a silicon substrate, the silicon substrate is placed in the bearing groove of the SiC-C base. Silicon will be deposited on the surface of the silicon substrate and other areas of the base. After the epitaxial growth is completed, the silicon wafer after epitaxial growth in the bearing groove is taken out; the deposited silicon on the surface of the base is then cleaned with HCl gas flow to ensure the recycling of the base. However, in the process of cleaning with HCl gas flow, the surface of the base without silicon deposition and the bearing groove after the wafer is taken out are completely exposed to a large flow of HCl, resulting in direct contact between the surface SiC and HCl, which is very easy to corrode the exposed parts, resulting in coating shedding, perforation, black spots and other failure phenomena during use, affecting the quality of the silicon wafer. Therefore, it is necessary to judge the corrosion resistance of the SiC-C base and select a SiC-C base with better corrosion resistance to avoid affecting the quality of the silicon wafer.
[0004] At present, the commonly used methods for judging the corrosion resistance of SiC-C bases are hydrothermal corrosion and Cl2 corrosion. The hydrothermal corrosion judgment method takes 7 to 60 days to have obvious corrosion effects. The corrosion cycle is long and the detection efficiency cannot meet the needs of practical applications. Summary of the invention
[0005] The purpose of the present invention is to provide a method for detecting the corrosion resistance of a SiC-C base and an application thereof. The detection method provided by the present invention can accurately and effectively detect the corrosion resistance of a SiC-C base and has high detection efficiency.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for detecting the corrosion resistance of a SiC-C base, comprising the following steps:
[0008] (1) depositing a dot-shaped transition metal film distributed in a dot matrix on the surface of a SiC-C base sample to obtain a pretreated SiC-C base sample;
[0009] (2) corroding the pretreated SiC-C base sample obtained in step (1) in a mixed gas flow of HCl and H2 to obtain a corroded sample;
[0010] (3) Measuring the corrosion depth of the corrosion sample obtained in step (2).
[0011] Preferably, the material of the dot-shaped transition metal film in step (1) is Pt, Cr or Ni.
[0012] Preferably, in the step (1), the diameter of the dot-shaped transition metal film is 1 to 2 mm, and the thickness of the dot-shaped transition metal film is 30 to 60 nm.
[0013] Preferably, the deposition time in step (1) is 20 to 40 seconds, and the target-substrate distance of the deposition is 11 to 12 cm.
[0014] Preferably, in step (2), the flow rates of HCl and H2 are independently 5 to 20 L / min, and the flow ratio of HCl to H2 is 1:(0.5 to 1.5).
[0015] Preferably, the corrosion temperature in step (2) is 1000-1400° C., and the corrosion time is 40-80 hours.
[0016] Preferably, the process of heating to the corrosion temperature is programmed heating, comprising:
[0017] In the first stage, the temperature is first increased from room temperature to 500° C., and the heating rate of the first heating is 1 to 3° C. / min;
[0018] In the second stage, the temperature is raised from 500° C. to 1000-1400° C., and the second heating rate is 5-8° C. / min.
[0019] Preferably, corrosion pretreatment is performed after the programmed temperature rise is completed; the time of the corrosion pretreatment is 100 to 200 minutes, the atmosphere of the corrosion pretreatment is an inert atmosphere or nitrogen, and the pressure of the corrosion pretreatment is 60,000 to 90,000 Pa.
[0020] Preferably, cooling is performed after the corrosion, and the cooling rate is 3-5°C / min.
[0021] The present invention also provides an application of the detection method described in the above technical solution, wherein the corrosion depth is used to characterize the corrosion resistance of the SiC-C base sample; or the corrosion rate is calculated using the corrosion time of the detection method and the obtained corrosion depth, and the corrosion resistance of the SiC-C base sample is characterized by the corrosion rate.
[0022] The present invention provides a method for detecting the corrosion resistance of a SiC-C base, comprising the following steps: (1) depositing a dot-shaped transition metal film with a dot matrix distribution on the surface of a SiC-C base sample block to obtain a pretreated SiC-C base sample block; (2) corroding the pretreated SiC-C base sample block obtained in step (1) in a mixed gas flow of HCl and H2 to obtain a corroded sample block; and (3) measuring the corrosion depth of the corroded sample block obtained in step (2). The detection method provided by the present invention utilizes a mixed gas flow of HCl and H2 to corrode the SiC-C base, simulating the actual use environment of the SiC-C base, so that the morphology after corrosion is consistent with the morphology of the SiC-C base after failure due to use at the application end, which is convenient for detection; a transition metal is deposited on the surface of the SiC-C base to catalyze the corrosion of the SiC-C base by HCl, greatly improving the corrosion efficiency and effectively improving the detection rate; at the same time, a mixed gas flow of HCl and H2 is used to corrode the SiC-C base, and H2 is used as a carrier gas for HCl, which can evenly transport HCl to the corrosion area, ensure uniform corrosion of the SiC-C base, effectively improve the corrosion rate, and further improve the detection efficiency; at the same time, H2 can combine with the intermediate byproducts of the HCl corrosion reaction of the SiC-C base, promote the forward reaction, and further improve the corrosion efficiency. The results of the embodiment show that the corrosion rate of the detection method provided by the present invention can reach 0.146×10 -2 ~0.302×10 -2 μm / min, and the corrosion depth or corrosion rate is used to accurately reflect the corrosion resistance of the SiC-C base in the service environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A detection device for the detection method of embodiment 1;
[0024] Figure 2 This is a macroscopic photograph of a SiC-C base sample after detection using the detection method of Example 1;
[0025] Figure 3 The corrosion depth of the SiC-C base sample block of Example 1 that has not been corroded using the white light detection method and the corrosion depth of the SiC-C base sample block that has been corroded using the detection method of Example 1 are shown;
[0026] Figure 4 The corrosion depth of the SiC-C base sample block of Example 2 which has not been corroded by the white light detection method and the corrosion depth of the SiC-C base sample block after being corroded by the detection method of Example 2 are shown;
[0027] Figure 5 The corrosion depth of the SiC-C base sample block of Example 3 that has not been corroded using the white light detection method and the corrosion depth of the SiC-C base sample block that has been corroded using the detection method of Example 3 are shown. DETAILED DESCRIPTION
[0028] The present invention provides a method for detecting the corrosion resistance of a SiC-C base, comprising the following steps:
[0029] (1) depositing a dot-shaped transition metal film distributed in a dot matrix on the surface of a SiC-C base sample to obtain a pretreated SiC-C base sample;
[0030] (2) corroding the pretreated SiC-C base sample obtained in step (1) in a mixed gas flow of HCl and H2 to obtain a corroded sample;
[0031] (3) Measuring the corrosion depth of the corrosion sample obtained in step (2).
[0032] The present invention deposits a dot-shaped transition metal film with dot-matrix distribution on the surface of a SiC-C base sample block to obtain a pretreated SiC-C base sample block.
[0033] As an embodiment of the present invention, the source of the SiC-C base sample can be a sample cut from an unused base; the size of the SiC-C base sample can be 20mm×20mm~40mm×40mm, or 25mm×25mm~30mm×30mm; the thickness of the SiC-C base sample can be 2~5mm, or 3~4mm; the thickness of the SiC coating in the SiC-C base sample can be 100~150μm, or 120~140μm, or 130~135μm.
[0034] As an embodiment of the present invention, the deposition method may be a magnetron sputtering method; the deposition device may be a high vacuum coater; the deposition power may be 50-100W, or 60-80W; the deposition time may be 20-40s, or 25-30s; the target-substrate distance of the deposition may be 11-12cm, or 11cm. In an embodiment of the present invention, the deposition device may specifically be a Leica-ace600. In the present invention, by limiting the deposition process parameters, uniform deposition of the transition metal film is achieved, excessive catalysis or incomplete catalysis of the corrosion position is avoided, and the detection efficiency is further improved.
[0035] As an embodiment of the present invention, the material of the dot-shaped transition metal film can be Pt, Cr or Ni, or can be Pt. In the present invention, by limiting the type of transition metal, the catalytic effect of the transition metal is improved, the corrosion efficiency is further improved, the corrosion cycle is shortened, and the detection efficiency is improved.
[0036] As an embodiment of the present invention, the diameter of the dot-shaped transition metal film can be 1-2 mm, or 1 mm; the thickness of the dot-shaped transition metal film can be 30-60 nm, or 40-55 nm, or 45-50 nm; the spacing of the lattice transition metal film can be 5-10 mm, or 6-9 mm, or 7-8 mm. In the present invention, by limiting the size of the transition metal film, the catalytic effect of the transition metal is fully exerted, and the catalytic efficiency is further improved.
[0037] As an embodiment of the present invention, the method for depositing a dot-shaped transition metal film with a lattice distribution can be: a ceramic cover plate with small holes is attached to the surface of the SiC-C base sample, and then a transition metal is deposited on the surface of the ceramic cover plate to obtain a lattice transition metal film; the aperture of the small holes on the ceramic cover plate can be 1 to 2 mm, or 1 mm. In the present invention, a ceramic cover plate with uniform small holes is used to limit the position of the transition metal film, so that the transition metal is evenly distributed on the surface of the SiC-C base, giving full play to the catalytic effect of the transition metal on HCl corrosion, and further improving the catalytic efficiency.
[0038] After obtaining the pretreated SiC-C base sample block, the present invention corrodes the pretreated SiC-C base sample block in a mixed gas flow of HCl and H2 to obtain a corroded sample block.
[0039] As an embodiment of the present invention, the flow rates of HCl and H2 can be independently 5-20 L / min, 8-15 L / min, or 10-12 L / min; the flow ratio of HCl to H2 can be 1:(0.5-1.5) or 1:1. In the present invention, by limiting the flow rates and flow ratios of HCl and H2, the corrosion effect of HCl is fully exerted to further increase the corrosion rate; at the same time, H2 is used as the carrier gas of HCl to uniformly transport HCl to the corrosion area, thereby ensuring uniform corrosion of the SiC-C base and further improving the detection efficiency.
[0040] As an embodiment of the present invention, the corrosion temperature can be 1000-1400°C, 1100-1300°C, or 1200-1250°C; the corrosion time can be 40-80h, 50-70h, or 60-65h. In the present invention, by limiting the process parameters of the corrosion process, the corrosion rate is promoted.
[0041] As an embodiment of the present invention, the process of heating to the corrosion temperature may be programmed heating, comprising:
[0042] In the first stage, the temperature is first increased from room temperature to 500° C., and the heating rate of the first heating can be 1-3° C. / min, or 2-2.5° C. / min;
[0043] The second stage is a second heating from 500°C to 1000-1400°C, and the second heating rate can be 5-8°C / min, or 6-7°C / min. In the present invention, by limiting the heating program of the corrosion temperature, it is avoided that the rapid heating causes a large thermal stress between the SiC coating and the graphite substrate due to the different degrees of thermal expansion, resulting in cracks or even detachment of the coating, which in turn affects the detection efficiency.
[0044] As an embodiment of the present invention, the programmed temperature rise can be carried out under a protective atmosphere; the protective atmosphere can be an inert atmosphere or nitrogen; the flow rate of the gas in the protective atmosphere can be 20 to 80 L / min, or 40 to 60 L / min. In the present invention, by introducing a protective atmosphere, air in the reaction system is removed to avoid oxidation side reactions occurring during the heating process and affecting the detection efficiency.
[0045] As an embodiment of the present invention, the pressure of the programmed temperature rise can be 60000-90000 Pa, or 70000-80000 Pa. In the present invention, by pressurizing during the temperature rise process as the basis for the subsequent corrosion reaction, the stability of the reaction system can still be ensured after the corrosive gas is introduced, further improving the detection efficiency.
[0046] As an embodiment of the present invention, vacuum treatment may be performed before the programmed temperature increase; the pressure of the vacuum treatment may be 100-300 Pa, 150-250 Pa, or 180-200 Pa. In the present invention, by limiting the process parameters of the vacuum treatment, the air in the reaction system is effectively removed, the influence of air on the corrosion reaction is avoided, and the detection efficiency is further improved.
[0047] As an embodiment of the present invention, corrosion pretreatment can be performed after the programmed temperature is completed; the atmosphere and pressure of the corrosion pretreatment can be the same as the atmosphere and pressure of the programmed temperature, which will not be repeated here; the time of the corrosion pretreatment can be 100 to 200 minutes, 120 to 180 minutes, or 150 to 160 minutes. In the present invention, thermal stress exists inside the silicon carbide coating during the programmed temperature rise process. By limiting the process parameters of the corrosion pretreatment process, the coating structure is stabilized, and at the same time, the temperature of the entire reaction system is made more uniform, the corrosion rate is increased, and the detection efficiency is further improved.
[0048] The present invention has no special limitation on the etching device, as long as it can achieve the mixed gas flow of HCl and H2 to enter at the upper end and exit at the lower end.
[0049] As an embodiment of the present invention, cooling can be performed after the etching is completed; the atmosphere and pressure of the cooling can be the same as the atmosphere and pressure of the programmed heating, which will not be repeated here; the cooling rate can be 3-5°C / min, 3.5-4.5°C / min, or 4°C / min. In the present invention, by limiting the process parameters of the cooling process, the coating is prevented from falling off due to the large temperature difference between the inside and outside, thereby affecting the test results.
[0050] After the corrosion sample is obtained, the corrosion depth of the corrosion sample is measured.
[0051] As an embodiment of the present invention, the measurement may be to detect the corrosion depths of any 2 to 6 corrosion areas of the point-shaped transition metal film and then take the average value to obtain the corrosion depth of the corrosion sample.
[0052] The present invention deposits transition metals on the surface of a SiC-C base, catalyzes HCl corrosion on the SiC-C base, and greatly improves corrosion efficiency; simultaneously, a mixed gas flow of HCl and H2 is used to corrode the SiC-C base, and H2 is used as a carrier gas for HCl, so that HCl can be uniformly transported to the corrosion area, thereby ensuring uniform corrosion of the SiC-C base and further improving detection efficiency; simultaneously, H2 can combine with an intermediate byproduct of a reaction of HCl corrosion on the SiC-C base, thereby promoting the reaction to proceed in the forward direction and further improving corrosion efficiency.
[0053] The present invention also provides an application of the detection method described in the above technical solution, wherein the corrosion depth is used to characterize the corrosion resistance of the SiC-C base sample; or the corrosion rate is calculated using the corrosion time of the detection method and the obtained corrosion depth, and the corrosion resistance of the SiC-C base sample is characterized by the corrosion rate.
[0054] In order to further illustrate the present invention, the detection method of the corrosion resistance of the SiC-C base provided by the present invention and its application are described in detail below in combination with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0055] Example 1
[0056] A method for detecting the corrosion resistance of a SiC-C base comprises the following steps:
[0057] (1) A ceramic cover plate with 1 mm uniform small holes was attached to the surface of a 20×20 mm, 3 mm thick SiC-C base sample (the grain size of the SiC coating was 70% 1-5 μm and 30% 5-10 μm), and a dot-shaped transition metal film with a dotted distribution was deposited by magnetron sputtering at a target-substrate distance of 3 cm and 80 W for 40 s to obtain a pretreated SiC-C base sample, wherein the dot-shaped transition metal film had a diameter of 1 mm and a thickness of 60 nm;
[0058] (2) Place the pretreated SiC-C base sample obtained in step (1) into Figure 1 In the shown etching furnace, to ensure air inlet at the upper end and air outlet at the lower end, vacuum treatment is performed to a pressure of 200Pa, and then 60L / min of argon is introduced and the pressure is maintained at 80000Pa for programmed temperature increase, firstly, the temperature is first increased to 500°C at a heating rate of 2°C / min, and then the temperature is secondly increased to 1000°C at a heating rate of 5°C / min, the argon atmosphere and pressure are maintained, and the etching pretreatment is performed for 100min, and a mixed gas flow of HCl and H2 is introduced at a flow rate of 10L / min independently, and the etching is performed at 1000°C and 80000Pa for 75h. After the etching is completed, the argon is introduced at a temperature reduction rate of 5°C / min under the condition of 60L / min of argon and the pressure is maintained at 80000Pa to obtain a corrosion sample block;
[0059] (3) Using a white light detection method, the corrosion depths of four randomly selected point-shaped corrosion areas of the transition metal film are detected, and the average value is taken to obtain the corrosion depth of the corrosion sample obtained in step (2).
[0060] The SiC-C base sample after being etched by the detection method of Example 1 was photographed, and the macroscopic photograph obtained was as follows: Figure 2 As shown. Figure 2 It can be seen that the surface of the SiC-C base sample with dotted transition metal film is obviously corroded, indicating that the transition metal can effectively increase the corrosion rate of the SiC coating on the surface of the SiC-C base sample.
[0061] Example 2
[0062] The only difference between Example 2 and Example 1 is that the grain size of the SiC coating in the SiC-C base sample is 50% 5-10 μm and 50% 20-30 μm, and the rest is the same as Example 1.
[0063] Example 3
[0064] The only difference between Example 3 and Example 1 is that the grain size of the SiC coating in the SiC-C base sample is 80% 10-20 μm and 20% 50-60 μm, and the rest is the same as Example 1.
[0065] The test results of the method for testing the corrosion resistance of the SiC-C base in Examples 1 to 3 are as follows: Figures 3 to 5 As shown in Table 1; Figures 3 to 5 The figures on the left in the middle represent the corrosion depth of the SiC-C base sample blocks that have not been corroded by the detection methods of Examples 1 to 3, respectively. Figures 3 to 5 The figures on the right side of the figure represent the corrosion depth of the SiC-C base sample after being corroded by the detection methods of Examples 1 to 3.
[0066] from Figures 3 to 5 It can be seen from the corrosion depth of the corrosion sample block after the detection method of the corrosion resistance of the SiC-C base in Examples 1 to 3, the corrosion depth of any four corrosion areas is selected, and the corrosion depth result obtained by taking the average value is shown in Table 1.
[0067] Table 1 Test results of the test method for the corrosion resistance of SiC-C base in Examples 1 to 3
[0068] Example 1 Example 2 Example 3 Corrosion depth (μm) 8.3172 13.5960 6.5698 Corrosion rate (μm / min) <![CDATA[0.185×10 -2 ]]> <![CDATA[0.302×10 -2 ]]> <![CDATA[0.146×10 -2 ]]>
[0069] It can be seen from Table 1 that the detection method provided by the present invention can make the corrosion rate of the SiC coating in the SiC-C base reach 0.146×10 -2 ~0.302×10 -2 μm / min, the corrosion rate is high, which can effectively improve the detection efficiency; at the same time, through comparison, it can be seen that the corrosion resistance of the SiC-C base sample of Example 3 is the best, the corrosion resistance of Example 1 is second, and the corrosion resistance of Example 2 is the worst.
[0070] The standard for judging the corrosion resistance of SiC-C base is: when the thickness of the transition metal film layer is between 30 and 60 nm, the corrosion rate of the qualified base will not exceed 0.4 μm / min after 40 to 50 hours of corrosion. It can be seen that the detection method provided by the present invention can detect whether the corrosion resistance of the base is qualified and whether it can be used normally.
[0071] Comparative Example 1
[0072] A high-temperature hydrothermal corrosion test was carried out on the SiC-C base sample in Example 2 using a static autoclave. The water medium used in the test was deionized water. The test temperature was 360±6°C and the pressure was 18.2±1.4MPa. After 60 days of corrosion, the corrosion depth of the corroded SiC-C base sample was detected.
[0073] After testing, it can be seen that the corrosion depth of the sample after hydrothermal corrosion in Comparative Example 1 is 10 μm, and the corrosion rate is 0.012×10 -2 μm / min.
[0074] By comparing Examples 1 to 3 with Comparative Example 1, it can be clearly seen that the detection method provided by the present invention takes a shorter time to achieve similar technical effects and has a higher corrosion rate. Therefore, it can be seen that the detection method provided by the present invention effectively improves the detection rate.
[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for detecting the corrosion resistance of a SiC-C base, comprising the following steps: (1) depositing a dot-shaped transition metal film distributed in a dot matrix on the surface of a SiC-C base sample to obtain a pretreated SiC-C base sample; (2) corroding the pretreated SiC-C base sample obtained in step (1) in a mixed gas flow of HCl and H2 to obtain a corroded sample; (3) Measuring the corrosion depth of the corrosion sample obtained in step (2).
2. The detection method according to claim 1, characterized in that: The material of the dot-shaped transition metal film in step (1) is Pt, Cr or Ni.
3. The detection method according to claim 1, characterized in that: In the step (1), the diameter of the dot-shaped transition metal film is 1 to 2 mm, and the thickness of the dot-shaped transition metal film is 30 to 60 nm.
4. The detection method according to claim 3, characterized in that: The deposition time in step (1) is 20 to 40 seconds, and the target-substrate distance of the deposition is 11 to 12 cm.
5. The detection method according to claim 1, characterized in that: In the step (2), the flow rates of HCl and H2 are independently 5 to 20 L / min, and the flow ratio of HCl to H2 is 1:(0.5 to 1.5).
6. The detection method according to claim 1, characterized in that: The etching temperature in step (2) is 1000-1400° C., and the etching time is 40-80 hours.
7. The detection method according to claim 6, characterized in that: The process of heating to the corrosion temperature is programmed heating, which includes: In the first stage, the temperature is first increased from room temperature to 500° C., and the heating rate of the first heating is 1 to 3° C. / min; In the second stage, the temperature is raised from 500° C. to 1000-1400° C., and the second heating rate is 5-8° C. / min.
8. The detection method according to claim 7, characterized in that: After the programmed temperature rise is completed, corrosion pretreatment is performed; the time of the corrosion pretreatment is 100 to 200 minutes, the atmosphere of the corrosion pretreatment is an inert atmosphere or nitrogen, and the pressure of the corrosion pretreatment is 60000 to 90000 Pa.
9. The detection method according to claim 6 or 7, characterized in that: The corrosion is followed by cooling, wherein the cooling rate is 3-5°C / min.
10. Use of the detection method according to any one of claims 1 to 9, characterized in that: The corrosion depth is used to characterize the corrosion resistance of the SiC-C base sample; or the corrosion rate is calculated using the corrosion time of the detection method and the obtained corrosion depth, and the corrosion resistance of the SiC-C base sample is characterized by the corrosion rate.
Citation Information
Patent Citations
Solid-phase sintering silicon carbide ceramic surface corrosion method
CN101165006A
Test method for evaluating corrosion resistance of coating
CN104266958A
Crystal silicon wafer corrosion rate testing method
CN112038247A
In-situ micro-nano indentation test system and method in ultrahigh-temperature water-oxygen environment
CN112229752A
Method for determining corrosion rate of transition metals in oxygen-containing media
RU2745243C1